Repetitions, Their Phonetic Features And Functions In Kurmanji Kurdish - Aveen Mohammed Hasan; Baydaa Mohammed Saeed Mustafa (European Scientific Journal, ESJ, 2016)
The study deals with the analysis of repetitions, their phonetic structures and functions as demonstrated in the organisation of talk-ininteraction in Kurdish. The repetitions are described as complex phonetic objects whose design has received no previous attention and are neglected by the scholars in the fields of discourse and conversation analysis studies in Kurdish. The main aims of the study are to identify the phonetic characteristics of repetitions in Kurdish, their functions and the relationship between differences in the phonetic features and their functions in speech. The study integrates the methodology of conversation analysis and impressionistic and instrumental phonetics to show how repetitions in a conversation are managed by the participants. The data used in this study comes from different types of natural speech, namely, face to face conversations, radio-phone-ins of Northern Kurdish. 27 cases of self repetitions have been analysed and they are lexical, phrasal and clausal with a range of syntactic forms. The study contributes to the theoretical issues of the prosody-pragmatics interface and participants’ understanding of naturally occurring discourse. It is hoped that such a study may contribute to language and information processing by providing a detailed analysis of patterns and functions of repetition in social interaction.